The Relevance of Essentialist Philosophy in Maintaining Moral Values in the Modern Era and the Perspective of Islamic Educational Philosophy - Azmalia Anastasya Marcella; Mikyal Kaisa Rasyid; Khabib Alwi (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2025)
The purpose of this study is to integrate the perspective of essentialism philosophy with moral values, how essentialism philosophy will make moral values the core of knowledge. For the method used, the author uses a qualitative approach through library research, which refers to various literature on essentialism philosophy in Islamic education. Data collection was carried out by examining various sources, both primary sources such as journals and proceedings, and secondary sources such as books and relevant articles obtained from Google Scholar. After the data was collected, interpretive analysis was carried out, and the research results were presented. The results of this study discuss the concept of essentialism philosophy, the relevance of essentialism in maintaining moral values in the modern era, and a comparison of the basic values of essentialism and Islam.